Creencias presentes en un grupo de patrulleros de la unidad del Escuadrón Móvil Anti Disturbios (ESMAD) de la Policía Metropolitana de Bogotá frente al abuso policial por parte de uniformados de la Policía Nacional de Colombia (2019)
The following investigation has as intention explore the present beliefs in a group of patrol crafts of the unit ESMAD opposite to the abuse of police. This project was realized in order to analyze possible motives on this phenomenon that generates an important impact for the society as for the police community. This investigation was realized taking the social psychology as a reference, the situations allow to determine what one thinks of the others, in how they influence the different behaviors and in how they relate between yes, and this is identified from the narratives that face a situation.